PENINGKATAN HASIL BELAJAR MENGGIRING BOLA DENGAN METODE INQUIRY - Muh. Yusril (Jurnal Panrita, 2021)
This research aims to find out whether students' learning outcomes of Dribbling Learning In Football Games can be improved by using inquiry method. Instruments used in this research namely dribbling work tests on football games and motivational observation, cooperation and development of football movements.This research is Class Action Research (CAR). As for the subjects in this study are grade VIII 8students that consists of 28 students consisting of 13women and 15 men.The results of the study can be concluded that efforts to improve the results of dribbling learning in football games with inkuiry methods in grade VIII students of SMP Negeri 8 Palopo are characterized by an increase in the average grade of students. The average grade of students in pre-tinence activities was 70.67 with a completion percentage of 42.86%. The condition increased the average grade of students in cycle I by 73.74 and the completion percentage by 60.71%. However, the increase has not yet reached the previously set target. Then after moving on to cycle II the average grade of student football increased again by 80.82 with a completion percentage of 85.71%. This indicates that the previously set target has been reached so that research is stopped in cycle II. The dribbling ability in the game of learner football is increased by being marked by all students completed KKM (Minimum Completion Criteria) which is 75.